The Psychology of Social Conflict and Aggression. - Forgas, Joseph P. (Sydney Symposium of Social Psychology., 2011)
This book offers an informative, scholarly yet readable overview of recent advances in research on the nature, antecedents, management, and consequences of interpersonal and intergroup conflict and aggression.